OPTIMASI EKSTRAKSI ULTRASONIK DENGAN VARIASI RASIO BAHAN : PELARUT DAN LAMA EKSTRAKSI TERHADAP KADAR FLAVONOID TOTAL DAUN KELOR (Moringa oleifera Lam) - Bintang Senayudha Wirasakti (2020)
Moringa plant is one of the most useful plant. The most used part of the plant is Moringa leaves. Moringa leaves contain high antioxidant compounds. One of the antioxidant contained in Moringa leaves are flavonoids. Antioxidant compound can prevent the forming of oxidation reaction so it is often used as an anti-free radicals. The selection of the extraction method is very important because the extraction results will reflect the level of success of the method. The nine group based on two variant, solid-to-solvent ratio (1:5, 1:10, 1:15) and extraction time (10, 20, 30 minute) were tested based on their, rendement, fitochemical test, and total flavonoid content. Result of this study showed the highest rendement is extraction with 1:15 solid-to-solvent ratio and 10 minute extraction time with 60,42% rendement, and the most optimized extraction basend on total flavonoid content is extraction with 1:5 solid-to-solvent ratio and 10 minute extraction with total flavonoid content of 2,69%.